PENDEKATAN TEKNOLOGI DALAM PENGEMBANGAN KURIKULUM PENDIDIKAN DI SEKOLAH DASAR - Subagyo, Roni; Fitri Puji Rahmawati; Anik Ghufron (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to explore the use of technological approaches in the development of educational curricula in elementary schools. The method used in this research is a literature review. The researcher utilized various written sources such as articles, journals, and documents relevant to this study. The results show that the technological approach can enhance the effectiveness and efficiency of learning and facilitate students in achieving established learning goals. However, some obstacles were also found, such as limited access to technology in the surrounding environment or difficulties in fully integrating technology into the curriculum. Therefore, the author provides practical recommendations for educators, policymakers, and other stakeholders to optimize the use of technology in elementary education in Indonesia.